Performance Evaluation of 120 kWp On-Grid Photovoltaic Power Plants after Five Years of Operation - Umam, Mukhamad Faeshol; Patria, Mochamad Febrian Adhi; Affandi , Dani Maulana; Nugraha, Deva Harry; Kurniawan, Hanifah Dwi; Ramadani, Havid Pandu (Indonesian Journal of Energy, 2025)
This study assesses the five-year operational performance of a 120 kWp grid-connected rooftop photovoltaic (PV) power plant with multiple locations in Blora, Central Java, Indonesia.  By analyzing real-world energy yield, degradation rates, and climate-related impacts, the study identifies key environmental and technical factors influencing PV efficiency.  Performance data from 2020 to 2025 show varying degrees of degradation across sites, with Widya Patra 3 showing the greatest reduction (51.09%), and Widya Patra 2 showing the least (12.5%).  The study confirms that dust accumulation, shading, temperature fluctuations, and humidity have a significant impact on long-term efficiency.  Climate variables such as sunshine duration, rainfall intensity, and wind speed were found to have a direct relationship with energy yield.  These findings highlight the importance of regular maintenance, proactive cleaning strategies, and optimized PV system designs for better performance and sustainability in tropical climates.  The study sheds light on future PV reliability improvements, guiding the implementation of climate-resilient strategies in solar energy development.